رواج نامۂ سوات میں موجود کارخانہ جات اور مزدوران کے متعلق والئ سوات کے فرامین کا شرعی و تحقیقی جائزہ : Industrial and Labour Laws at the Regime of Wali-e-Swat: A Critical and Jurisprudential Analysis from the Perspective of Islamic Law (Al-NASR, 2024)
The rulers of colonies, in the Great Britain regime, tried to control their citizen through various techniques. Among these methods, the most important was to make such laws which are in line with the custom, religion, norms and culture of the concerned population.  Wali Swat, a ruler of the rural area of Pakistan, adopted the same approach. While following this, he made such laws and issued such orders which were either based on Sharī‘ah (Islamic law) or in compliance to it. This approach, in fact, worked for him; as the people of region were the stern follower of Sharī‘ah.  Following this tactic, the industrial and labour laws, at that time, were also made in line with the doctrines of Islamic law. The present research endeavour aims to look critically whether such laws were truly in line with the principles of  Islamic law or that was a mere claim. Finding elucidates, with solid arguments, that majority of such laws were based on Sharī‘ah; however, some laws were either based on local custom or based on conventional law.  The content analysis technique, being the most important tool of qualitative research, had been used for the investigation of the issue under discussion. Being followed by the people of Swat, the laws of that time are critically analysed in the legal literature of the Hanafī School; but other schools also have been resorted whenever deem appropriate.
Keywords: Law; Islamic Law; Sharī‘ah; Jurists; Hanafī School; Labour Laws; Industrial Laws; Wali Swat; Swat; Islamic Jurisprudence; Islamic Literature